Faktor- Faktor Yang Mempengaruhi Keputusan Pembelian Di Toko Tembakau Nusantara Melalui Word Of Mouth - Mukharomah Mukharomah; Bayu Kurniawan; Rita Meiriyanti (EBISMAN eBisnis Manajemen, 2023)
This study aims to determine the influence of product quality and price on the purchase decision of tobacco products at Nusantara Tobacco Shop through word of mouth. This type of research uses quantitative research methods and the data used in this study is primary data. The population in this study was customers of Toko Tobacco Nusantara, this study used purposive sampling techniques with a saturated sample of 98 respondents. The measurement of this study uses the Likert scale which is then processed with SmartPLS 4.0 program analysis.The results of this study show that product quality affects purchasing decisions with a P-Value value of (0.004), price affects purchasing decisions with a P-Value value of (0.030) and word of mouth affects purchasing decisions with a P-Value value of (0.012). Word of mout is able to mediate product quality against purchasing decisions with a P-Value of (0.039). Word of mout is able to mediate price against purchase decisions with a P-Value of (0.041). Product quality has an influence on word of mouth with a P-Value of (0.000). Price has an influence on word of mouth with a P-Value of (0.000).